Soil Carbon Storage 2018
DOI: 10.1016/b978-0-12-812766-7.00009-3
|View full text |Cite
|
Sign up to set email alerts
|

Projecting Soil C Under Future Climate and Land-Use Scenarios (Modeling)

Abstract: Soil carbon sequestration can be estimated from field to global scale using numerical 9 soil/ecosystem models. In this chapter we describe the structure and development of models 10 that have been widely used at international level, from simple models that include carbon 11 only to model that include descriptions of the dynamics of a range of nutrients. We also 12 present examples of the application from field to global scale of different models to answer a 13 range of different questions on the impact of land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 94 publications
0
14
0
Order By: Relevance
“…The complex approach to this issue is to identify the contribution of the mining sector to society over long periods of time [5]. It can be seen that it develops [10]:…”
Section: Implications Of the Mining Industry For The Social Dimensionmentioning
confidence: 99%
See 2 more Smart Citations
“…The complex approach to this issue is to identify the contribution of the mining sector to society over long periods of time [5]. It can be seen that it develops [10]:…”
Section: Implications Of the Mining Industry For The Social Dimensionmentioning
confidence: 99%
“…But most organizations are involved in this approach as a condition of existence in the business environment. In the mining industry, the number of reports of involvement in sustainability is lower at the national level, but at the international level the implications are more numerous [5,7,[9][10][11].…”
Section: Initiatives To Assess the Social Dimensionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to apply process based models in largescale simulations due to high computational costs and large information requirements (Dondini et al, 2018). They need to be either evaluated for the local conditions or applied with caution.…”
Section: Process-based Modelingmentioning
confidence: 99%
“…Globally, several investments have been made in this industry, but the inherited negative image is often an obstacle. It is shown that [7,8] over 80% of the world's largest companies in the extractive industry publish information on environmental, economic, and social performance [9]. This paper aims to assess the impact and implications of the mining industry on the objectives of sustainable development and reducing the footprint on the environment.…”
Section: Introductionmentioning
confidence: 99%